Semantics analysis of Ratatouille movie: The lexical ambiguity in English - Kamilah, Athirah Putri; Wijaya, Beni; Nadjmuddin, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
The importance of understanding meaning in context is highly paramount in movies. This linguistics research attempts to identify the utilization and prevalent use of homophones and homographs in the Disney animated film “Ratatouille.” This study highlighted semantics analysis through three characters; Remy, Alfredo Linguini, and Colette Tatou by analyzing their dialogues and narratives according to the spellings, writings, and meanings. With a total discovery of 313 words out of 920 dialogues, it was found that this film more maneuvered towards homophone, with Linguini as the leading conveyor with 75 words in hand. On the other side, Remy followed second as the provider of homographs with a sum of 60 words. These number show how lexical ambiguity can lead to misunderstanding if there are multiple meanings associated with the word. Thus, these results can not only contribute linguistically to comprehending the storytelling experience in the film, but also indicate that despite being the harder one, homophone words were used more commonly than homographs.